1988
DOI: 10.1063/1.99951
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomorphic In0.53Ga0.47As/AlAs/InAs resonant tunneling diodes with peak-to-valley current ratios of 30 at room temperature

Abstract: Pseudomorphic In0.53 Ga0.47 As/AlAs/InAs resonant tunneling diodes have been grown on InP substrates by molecular beam epitaxy. Peak-to-valley current ratios as high as 30 at 300 K and 63 at 77 K are obtained on a structure with barriers of ten atomic layers AlAs, and a well consisting of three atomic layers of In0.53 Ga0.47 As, six atomic layers of InAs, and three atomic layers of In0.53 Ga0.47 As. For comparison pseudomorphic In0.53 Ga0.47 As/AlAs with In0.53 Ga0.47 As well structures have also been fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…In this regard, a variation of the InGaAs/AlAs system has come to the fore. It contains a modified InGaAs well with extra In inserted, either in the form of a higher alloy concentration than called for by lattice matching or a small number of pure InAs central layers [72]. Either way, the extra In lowers the resonance energy in the well so that the peak voltage is lowered correspondingly.…”
Section: B Materials and Structural Considerationsmentioning
confidence: 99%
“…In this regard, a variation of the InGaAs/AlAs system has come to the fore. It contains a modified InGaAs well with extra In inserted, either in the form of a higher alloy concentration than called for by lattice matching or a small number of pure InAs central layers [72]. Either way, the extra In lowers the resonance energy in the well so that the peak voltage is lowered correspondingly.…”
Section: B Materials and Structural Considerationsmentioning
confidence: 99%
“…Low alloy broadening is required for good device performance to minimise alloy scattering. In 1988, Broekaert et al reported a high PVCR of 30 at 300 K for a InGaAs/AlAs/InAs structure with AlAs barriers of ten atomic layers for a peak current density of 6 kA/cm 2 [44]. This was achieved by the incorporation of binary InAs in the QW to reduce alloy scattering.…”
Section: Well-width Dependent Luminescence Characteristicsmentioning
confidence: 99%
“…The initial measurements done by Broekaert et al, 10 show that, in an In 0.53 Ga 0.47 As/AlAs/InAs structure grown on InP substrate, the PCD for the resonant tunneling through the second energy level is almost ten times greater than the PCD associated with the first energy level for the same structure. However, the peak voltage for the second resonant energy level is so high (ϳ4.1 V) that it makes the use of tunneling through the second level highly impractical for any application.…”
Section: ͓S0003-6951͑97͒02821-0͔mentioning
confidence: 99%